The Role Of Social Services In Tackling Beggars In Malang City (Study At Malang City Social Office) - Santi Bintara Wati; Syamsul Sukmono Edy; Eka Setyowati (Publikasi Indonesia, 2023)
Malang City Social Bureau is a place of social services for homeless people. Homeless people are often placed in poor positions by economic means and consequently need to be given a boost in the form of coaching. The events that are intertwined even vagrants and dumbbells have not been handed over coaching. What exactly is the strategy for implementing homeless coaching? The purpose of this research is to identify the contribution of social bureaus in the city of Malang in overcoming homelessness in the city of Malang and what factors influence the contribution of social bureaus in overcoming vagrants in the city of Malang. The philosophy used as an analytical tool in this research is a philosophy about art, as well as a philosophy of overcoming. The type of research used is qualitative, a system of views or an incident in the current era with the meaning of sharing reflections analytically about reality or events in the field with a descriptive approach. The method of collecting information uses questions and answers as well as monitoring. The method of information analysis used in this research is to describe information with the results of questions and answers. Based on the results of this research, the contribution of social bureaus in overcoming homelessness in the city of Malang does not run efficiently, because there are efforts that have not been realized by the social bureau in the city of Malang in overcoming solutions.